Fiqh Teachers’ Efforts to Improve Competency Pedagogy in Madrasah - Imam Hambali (Edumaspul: Jurnal Pendidikan, 2025)
This research is motivated by the fact that teachers really determine student success, especially in relation to the teaching and learning process and shaping student competence to be better. Learning quality can be said to be a description of the good or bad results and understanding achieved by students after learning activities are carried out. Fiqh as one of the compulsory subjects at Madrasas in particular, occupies a strategic role in efforts to shape personality, instill Islamic sharia values, attitudes, intelligence, knowledge, understanding and behavior in accordance with Islamic sharia. The aim of this research is to determine the efforts of fiqh teachers to improve pedagogical competence in Madrasas. This research method uses qualitative research methods. The results of the research show that efforts to increase the pedagogical competence of fiqh teachers include: (1) making an effort to impart knowledge with love and sincerity, (2) conveying knowledge interestingly and enthusiastically, (3) getting used to asking questions for self-improvement, (4) making reading a habit, (5) attending seminars and training. Pedagogical competence has a very important role in teaching and learning activities, namely making it easier for teachers to convey material to students and teachers can apply various learning strategies to create enjoyable teaching and learning activities.